POSSIBILITIES OF RECOVERY AND VISUALIZATION OF LATENT PAPILLAE PATTERN PRINTS FROM THE SKIN OF A DEAD PERSON. RESULTS OF A SERIES OF EXPERIMENTS - Zīle, Aelita (Administrative and Criminal Justice, 2017)
The aim of the experiment conducted by the author was to research and analyse the possibilities of leaving of latent papillae pattern prints on the skin of a dead person by natural sweat and grease substance, possibilities of transferring of them to papillae pattern prints (trace-leaving object) from other parts of the body without additional sweat and grease substance, as well as possibilities of recovery and visualization of these prints using combinations of different adhesive reagents and reagents used for their recovery. In the framework of a series of experiments 1419 latent papillae pattern prints were deposited onto the skin of 43 dead persons. 33 of them were men aged 25 to 81 years and 10 women aged 37 to 95 years. Experimental papillae pattern prints were deposited onto such parts of the body: neck, shoulders, upper arm and forearm, thigh and shin, ankles, chest, abdomen and hips. Prints were deposited by simulating the mechanism of formation of grip and pressure prints. The length of the contact was from 10 to 180 seconds. Depositing them the variable crushing force was used. After visualization and recovery of experimentally deposited latent papillae pattern prints 37 of them were recognized as valid for person identification, 66 prints contained papillae patterns, but there were not enough special features of papillae pattern to recognize them as valid for person identification. Shape of finger phalanges and palm was reflected in 202 prints, but 1114 experimentally deposited prints were not visible. The summary of the results obtained during the experiment let to conclude that the most papillae pattern prints valid for person identification were deposited onto the left and right side of the chest – 18 prints, onto the knee part of the right and the left leg – 6 prints, but onto the right and left upper arm – 3 prints. Swedish Black B-421000 and White silicone with paste hardener C-1400 (21 prints valid for person identification), Special Blower Black B-35000 and Gelatin Lifters White (FOMA) (9 prints valid for person identification), Swedish Black B-421000 and Gelatin Lifters White (FOMA) (4 prints valid for person identification were recognized as the best combinations of adhesive reagents and reagents used for recovery. The results obtained during the experiment also let to conclude that: - Microrelief of the skin (trace-perceiving object) does not always have an impact on the quality of a print; - A victim’s age and gender do not affect the quality of a print; - There is no particular proportionality between the number of deposited prints and the number of prints valid for identification.